An Empirical Study of the Factors Influencing Consumer Behaviour in the Electric Appliances Market - Małgorzata Łatuszyńska; Fatimah Furaiji; Agata Wawrzyniak (Contemporary Economics, 2012)
This study contributes to a deeper understanding of the impact of different factors on consumer buying behaviour. It analyses the relationship between several independent variables, such as cultural, social, personal, psychological and marketing mix factors, and consumer behaviour (as the dependent variable) in the electric appliances market. The purpose of this study is to determine the factors affecting consumer preferences and behaviour in the electric appliances market in Iraq. The data employed to analyse the factors influencing consumers' purchase decision-making processes were obtained through a questionnaire that was conducted in December 2011 in Basra, a city in southern Iraq. The major findings of the study indicated that, overall, the set of independent variables are weakly associated with the dependent variable. However, the in-depth analysis found that social factors, physical factors, and marketing mix elements are strongly associated with consumer buying behaviour. These analyses make it possible to discover consumer decision-making rules. The results may assist producers and retailers in understanding consumer behaviour and improving consumer satisfaction.
Keywords: D1; M3; 330; consumer behaviour; purchase decision making; decision-making process